The structure of waxy corn starch: Effect of granule size - Franco, Célia M. L. [UNESP]; Ciacco, César F.; Tavares, Débora Q. (Wiley, 1998)
The granules of waxy corn starch were isolated and various samples were separated by size and classified according to their average diameter in: non-separated granules (N), granules with diameter < 15 μm (S) and granules with diameter ≥ 15 μm (L). The samples were hydrolyzed by bacterial α-amylase and fungal amyloglucosidase. The starch granules remaining after enzymatic hydrolysis were analysed by X-ray diffraction and optical and scanning electron microscopy. Sephadex G-50 gel permeation chromatography of the dissolved residues from the hydrolysis of the N and S samples was performed directly and after successive enzymatic digestion with pullulanase and β-amylase. The results showed that the percentage of hydrolysis increased with a decrease in diameter. No apparent differences in waxy corn starch when observed under light and scanning electronic microscope were observed, regardless of diameter and enzyme action, although both large and small granules showed extensive surface corrosion after enzymatic attack. X-ray analysis suggested a decrease in the quantity of crystalline areas in the smaller granules, which would explain the high percentage of hydrolysis evidenced by these granules. The elution patterns of the α-glucans of both starches (N and S) were similar and reveled the presence of two fractions which were not susceptible to a-amylase and amyloglucosidase attack suggesting that these fractions were involved in the waxy corn starch crystalline regions. Debranching with pullulanase followed by gel-permeation chromatography showed that the amylopectins from the starch granules studied contained three groups of unit chains instead of the two reported in the literature.